PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. ADYA TOURS - Ahmad Gunawan (Jurnal Pengembangan Wiraswasta, 2017)
Transformation Leadership, Motivation and Satisfiction are the three factors of a few relatively large factors suspected to influence Performance on the PT. Adya Tours. These research aimed to determine the effect of Transformation Leadership, Motivation and Satisfiction toward Performance on the PT. Adya Tours.Research conducted at the PT. Adya Tours by taking 71 employees as the research sample, calculated using the Slovin formula of the total population of 240 employees  at  the  margin  of  error  of  10%.  Data  were collected by questionnaire instruments covered by the five rating scale from strongly disagree to strongly agree. Quantitative research was conducted by describing and analyzing research data. The multiple linier regression analysis and multiple determination coeficient are the statistic approach to data analysis.The study produced four major findings consistent with the hypothesis put forward, that are: 1) Transformation Leadership has a significant effect on Performance  in  a  positive  direction;  2)  Motivation  has  a  significant  effect  on Performance in a positive direction; 3) Satisfiction has a significant effect on Performance in a positive direction; 4) Transformation Leadership, Motivation and Satisfiction simultaneously influence 92.70% Performance variability.Base on the research finding, in order to increase Performance can be done by increasing Transformation Leadership, Motivation and Satisfiction. Kata kunci:Transformation Leadership, Motivation, Satisfaction, Performance